Exposure to mosquito coil and biomass fuel smoke and respiratory health in rural Tamil Nadu, India. (29th April 2021) - Rao, Sudha Ramachandra; Chitra, Grace A; Elavarasu, G; Kamaraj, P; Kaliaperumal, Kanagasabai; Kaur, Prabhdeep
Abstract: Background: Mosquito coil smoke, along with biomass fuel smoke, are sources of indoor air pollution. Biomass fuel smoke has been studied as a risk factor for poor respiratory outcomes. However, in an Indian context, few studies examine the effect of mosquito coil exposure on poor respiratory outcomes at the community level. Objectives: To estimate the prevalence of the biomass fuel and mosquito coil use and to determine the association between the use of bio-mass fuel and mosquito coil and poor respiratory health. Methods: A cross-sectional survey of 4662 individuals (above the age of 30 years) was conducted using a pre-tested questionnaire. Trained interviewers collected data on current and past use of biomass fuels and mosquito coils, usage practices and respiratory health. We computed proportions for exposure variables namely biomass fuel, mosquito coil use and other covariates. We conducted univariate analysis, followed by multivariate logistic regression. Results: The prevalence of ever use of biomass fuels was high (wood: 97.9%; cow dung cake: 76.0% and crop residue: 54.4%). Current use of wood, cow dung cake and crop residue was prevalent among 75.7, 24.3 and 30.9% respondents, respectively. Almost 70% of respondents had ever used mosquito coils, whereas 54% were current users. Overall, 5.5% respondents had poor respiratory health either due to chronic bronchitis or asthma. In multivariate analysis, use of combination of all three biomass fuel types (adjusted odds ratio [AOR] 1.69, 95% confidence interval [CI]: 1.13–2.54) and use of mosquito coil more than or equal to 5 days per week (AOR 1.43, 95% CI: 1.04–1.99) were associated with poor respiratory health after adjusting for covariates age, gender, smoking, kitchen type and for each other. Conclusions: Use of biomass fuels and mosquito coils was high in the study population and was associated with poor respiratory health. Therefore, mosquito coil smoke should also be considered an important source of indoor air pollution, similar to biomass fuel exposure. Community education about these sources of indoor air pollution and increased coverage of cleaner fuels and alternative mosquito control methods should be the way forward in the rural areas.